1987
DOI: 10.1093/ajcn/46.4.681
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of diet, athletic activity, menstrual status, and bone density in collegiate women

Abstract: We undertook a case-control study to examine the effect of nutritional factors on menstrual function and bone density in collegiate athletes. Three groups, matched with respect to age, height, and weight, were studied: eumenorrheic collegiate athletes, oligomenorrheic collegiate athletes, and eumenorrheic sedentary collegiate control subjects. Menarche was delayed in the eumenorrheic (13.1 y) and oligomenorrheic (14.3 y) athletic groups compared with the sedentary control subjects (12.2 y) (p less than 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1
3

Year Published

1989
1989
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 31 publications
0
24
1
3
Order By: Relevance
“…Numerous studies have shown a correlation between menstrual irregularities and incidence of scoliosis and stress fractures among athletes (Cann et al 1984, Drinkwater et al 1984, Lindberg et al 1984, Marcus et al 1985, Warren et al 1986, Lloyd et al 1987, Barrow & Saha 1988. In one study, scoliosis was reported in 24% of ballet dancers, much higher than that in the general population; 83% of dancers with scoliosis had delayed menarche, whereas only 54% of dancers without scoliosis reported delayed menarche (Warren et al 1986).…”
Section: Skeletal Problemsmentioning
confidence: 99%
“…Numerous studies have shown a correlation between menstrual irregularities and incidence of scoliosis and stress fractures among athletes (Cann et al 1984, Drinkwater et al 1984, Lindberg et al 1984, Marcus et al 1985, Warren et al 1986, Lloyd et al 1987, Barrow & Saha 1988. In one study, scoliosis was reported in 24% of ballet dancers, much higher than that in the general population; 83% of dancers with scoliosis had delayed menarche, whereas only 54% of dancers without scoliosis reported delayed menarche (Warren et al 1986).…”
Section: Skeletal Problemsmentioning
confidence: 99%
“…Lloyd et al (1987) encontraram uma relação positiva entre o consumo de fibras e as irregularidades menstruais. O aumento deste consumo também está relacionado com alterações no metabolismo do estrógeno.…”
Section: Inadequação Nutricionalunclassified
“…No entanto, atletas com baixo consumo de energia têm ingestão protéica inferior à daquelas com consumo energético normal. Assim, estudos mostraram que a ingestão protéica em si não possui relação com as irregularidades menstruais (Hale, 1984;Lloyd et al, 1987;Fruth & Worrell, 1995).…”
Section: Inadequação Nutricionalunclassified
“…Marcus et al (33) More specifically, Lloyd et al (29) suggested that a high fiber intake could be considered a cause of menstrual irregularity. In contrast, Nelson et a1 (37) found no difference in fiber consumption between their amenorrheic and eumenorrheic subjects.…”
Section: Training Parametersmentioning
confidence: 99%
“…Criteria for amenorrhea have ranged from 3 to 12 months without menstruation (12,32,34). Oligomenorrhea has been used as a somewhat arbitrary term, denoting irregular cycles occurring from 33-to 90-day intervals (10,29,48,49). Eumenorrhea describes a normal menstrual pattern of 10-13 menses per year (12,32,40).…”
mentioning
confidence: 99%